A critical review on corrosion of compression ignition (CI) engine parts by biodiesel and biodiesel blends and its inhibition - Singh B.; Korstad J.; Sharma Y.C. (My University, 2025)
This paper reviews the effects of corrosion on the engine parts that come in contact with a newly developed biodiesel fuel and its petrodiesel blend. Copper, aluminum, copper alloys (bronze), and elastomers caused significant levels of corrosiveness in biodiesel and biodiesel blend as opposed to low corrosion with petrodiesel. Specimens of stainless steel showed significant resistance to corrosion in biodiesel samples as compared to copper, aluminum, and copper alloys, but the level of corrosion was still higher than that in petrodiesel. Common methods adopted for measurement of corrosion include weight loss through static emersion tests, and electrochemical techniques by electrochemical impedance spectroscopy or on Potentiostat/Galvanostat. The surfaces of the specific metal strips were analyzed by optical, scanning electron, and atomic force microscopy, revealing the nature and extent of corrosion. Fourier Transform Infrared Spectroscopy revealed formation of secondary product due to degradation, and X-ray diffractometer revealed formation of a new phase in the metal strips exposed to biodiesel and its blend with mineral diesel. Biodiesel seemed to degrade due to auto-oxidation and presence of moisture to secondary products that enhanced the corrosion rate. The problem related to the use of non-compatible materials as engine parts for biodiesel-run vehicles is dual in nature. The engine part in contact with the fuel is corroded as a result of fuel degradation, causing the fuel to go further off-specification. © 2012 Elsevier Ltd. All rights reserved.